Prediction of canine and premolar size using the widths of various permanent teeth combinations: A cross-sectional study - Kalasandhya Vanjari; Sivakumar Nuvvula; Rekhalakshmi Kamatham (Wolters Kluwer Medknow Publications, 2015)
Aims: To suggest the best predictor/s for determining the mesio-distal widths (MDWs) of canines (C) and premolars (Ps), and propose regression equation/s for hitherto unreported population. Methods: Impressions of maxillary and mandibular arches were made for 201 children (100 boys and 101 girls; age range: 11-15 years) who met the inclusion criteria and poured with dental stone. The maximum MDWs of all the permanent teeth were measured using digital vernier caliper. Thirty-three possible combinations (patterns) of permanent maxillary and mandibular first molars, central and lateral incisors were framed and correlated with MDWs of C and Ps using Pearson correlation test. Results: There were significant correlations between the considered patterns and MDWs of C and Ps, with difference noted between girls (range of r: 0.34-0.66) and boys (range of r: 0.28-0.77). Simple linear and multiple regression equations for boys, girls, and combined sample were determined to predict MDW of C and Ps in both the arches. Conclusions: The accuracy of prediction improved considerably with the inclusion of as many teeth as possible in the regression equations. The newly proposed equations based on the erupted teeth may be considered clinically useful for space analysis in the considered population.